Leukocytoclastic vasculitis associated with multifocal sensory neuropathy responsive to intravenous immunoglobulins: a case report. - Cama, Elena; Ferranti, Martina; Cacciavillani, Mario; Schiavon, Franco; Felicetti, Mara; Abriani, Chiara; Alaibac, Mauro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Leukocytoclastic vasculitis (LCV) is a common form of small-vessel vasculitis, which commonly presents as palpable purpura or petechiae, caused by deposition of circulating immune complexes on vessels walls that attracts granulocytes which damage the vascular endothelium and leading to erythrocytes extravasation. The skin is the most commonly involved organ, but also renal, gastrointestinal, pulmonary, cardiovascular and neurological systems may be affected. Skin lesions may be the initial signs of systemic vasculitis. Systemic symptoms may be present, such us fever, myalgia, abdominal pain and arthralgia. The presence of neuropathy/mononeuritis multiplex is expression of severe vasculitic involvement. Herein, we describe the case of a patient with leucocytoclastic vasculitis associated to sensitive neuropathy, responsive to intravenous immunoglobulins (IGIV) therapy, after the failure of classic systemic treatments.